Optimizing construction project completion: A risk-based approach - Ummi, Nurul; Setiawan, Hadi; Katili, Putiri Bhuana; Rahmawati, Virda Ayu (Journal Industrial Servicess, 2024)
A construction company has a significant issue within the project planning division in determining which construction projects to undertake, as the company only assesses them based on feasibility studies and overall project risks. To support the decision-making process in selecting construction project resolutions, research was conducted to propose selections based on risk criteria. This research aims to establish the risk criteria used, determine the ratings of risk criteria and sub-criteria, and identify project alternatives with the lowest risk ratings. From the data processing results, the risk criteria utilized are contractor risk, financial risk, environmental and natural risk, quality risk, and material risk. Using the Analytical Hierarchy Process manual method and Expert Choice 11 software, the ratings for contractor risk are 46%, financial risk 16.2%, environmental & natural risk 5%, quality risk 22.8%, and material risk 10.1%. Sub-criteria risk ratings are as follows: experience 15.2%, performance 30.8%, project funds 13.1%, budget increase 3.1%, social disturbances 3.5%, natural events 1.5%, material quality 8%, design quality 7.5%, building quality 7.2%, material delay 5.9%, and material specification 4.1%. The construction project alternative with the lowest risk rating is the guest house construction project at 0.132. Therefore, the guest house construction project is proposed for immediate prioritized completion.